Influence Nordic Hamstring Exercises on Increasing Hamstring Muscle Flexibility in Athletes Jakarta State University Futsal - darmawan, Cahyadi; Yuliana, Ela; Diyananda, Dzulfiqar; Purba, Ruliando Hasea (Universitas Negeri Jakarta, 2025)
Flexibility muscle hamstrings for futsal athletes have role important to support performance physique like acceleration and running fast , and prevent injury . This study aims to determine influence Nordic Hamstring exercises against improvement flexibility hamstring muscles in futsal athletes at Jakarta State University. This study used approach one group test -posttest design. A total of 15 samples study get treatment exercise Nordic hamstring s as many as 16 meetings . To find out influence from exercise nordic hamstring against improvement flexibility hamstring muscles using instrument sit and reach with tool flexometer . Research results disclose there is significant difference​ in a way statistics on flexibility hamstring muscles before and after do exercise Nordic hamstring (p = 0.001 or p < 0.05). With thus can concluded that exercise nordic hamstring effect positive to improvement flexibility hamstring muscles in futsal athletes at Jakarta State University. This study recommends use exercise Nordic hamstring as part from exercise programs for flexibility extremities down and up performance in futsal athletes .